RELATIVE MOVEMENT OF GRAIN COMPONENTS ACROSS FINS - Denis Konstantinovich Muratov (Advanced Engineering Research)
Values of wheat corn and chaff motion on the fin upwards and downwards from ? elevation corner of the fin for various ?B air velocities at one vibration period — Т = 2?/? — of the top screen are defined. The screen opening angles and air velocities at which grain will slide on the fin only downwards, and the opening angles and air velocities at which short chaff will slide on the fin only upwards, are determined. The inclined airflow parameters and fin elevation corner in the lip screen front when grain actively displaces on the fins downwards and gets under the screen are considered. Appropriate recommendations are made.